Whispering gallery mode of coated micro-bottle resonator using acrylate polymer for humidity sensing / Meisam Parsa Pour - Meisam, Parsa Pour (2018)
In recent years, Micro-Bottle Resonator (MBR) has attracted an excessive attention on account of its various applications such as sensors, lasing and filters. Compared to the other Optical Micro-Resonators (OMRs) it has some advantages of fast tunability through the strain application, better control over the coupling by optical tapered microfiber and in the spectrum the probability of attaining a great number of equally-spaced modes. The MBR was fabricated with an SMF-28 silica optical fiber by “soften-and-compress” method which created a bulge area on the fiber to become formed as bottle shape. In this research report used two method of MBR. First method: we have successfully studied the comparison of three the different size of tapered microfiber through Micro Bottle Resonator (MBR) for humidity sensing. A “soften-and-compress” technique has used to form the MBR with midriff diameter of